Risk management in a furniture factory: a case study - Gama de Moraes, Thaís; Randow de Freitas, Rodrigo; Quaresma Gomes, Keydson; Padovani Xavier, Thiago (Latin American Journal of Energy Research, 2022)
The furniture industry in Brazil has just over twenty thousand factories. Despite its importance to the economy, the industry faces problems directly related to low productivity and reduced competitiveness. When talking about low productivity and the need to maintain the business, risk management and process mapping emerge as tools that can help an organization in these aspects. There are several risk management techniques and studies on the topic within the furniture industries that have already been carried out. However, the techniques have limitations that must be considered. In this work, a study was carried out in a furniture industry in the North of Espírito Santo that classifies the risks according to their probabilities and impact. From this classification, a risk matrix is used to determine the degree of the risks studied and propose measures of control to minimize them. Therefore, this work aims to propose a new management methodology using process mapping. This methodology complements those that already exist and can be applied and adapted to other production sectors.